Walking on the tightrope between moderation and radicalisation: the first 100 days of the Meloni government - Marianna Griffini (QOE-IJES, 2023)
As the fatal grip of the Covid-19 pandemic started to ease, in summer 2022 Italy underwent seismic political developments, which saw the establishment of the first totally populist radical right government in Italian history. On 25 September 2022, the general elections shook up the Italian political scene, with Fratelli d’Italia (FdI) scoring a resounding victory that earned the party the seat of the Prime Minister. Despite fears of a radicalisation of FdI resulting in a neofascist government, evidence points in a different direction. Therefore, the aim of this article is to investigate whether, in the first 100 days in government, FdI moderated, radicalised, or displayed continuity with its trademark ideology and manifesto pledges. While acknowledging the copious amount of bills, decrees, and laws proposed by the governing coalition, as well as a plethora of speeches they released, in the interest of space, the scope of this article is circumscribed to the analysis of the new executive, with a special emphasis on FdI, in the timeframe between the election results and the first 100 days of the new government. Considering this evidence, this article argues that FdI is definitely acting as a populist radical right party, tilted towards moderation, and, mostly, continuity with the 2022 electoral pledges, albeit with some oscillations to radicalisation.